Race-specific genotypes of Pseudomonas syringae pv. tomato are defined by the presence of mobile DNA elements within the genome - Orfei, Benedetta; Pothier, Joël F.; Fenske, Linda; Blom, Jochen; Moretti, Chiaraluce; Buonaurio, Roberto; Smits, Theo H. M. (Frontiers in Plant Science, 2023)
Pseudomonas syringae pv. tomato is the causal agent of bacterial speck of tomato, an important disease that results in severe crop production losses worldwide. Currently, two races within phylogroup 01a (PG01a) are described for this pathogen. Race 0 strains have avirulence genes for the expression of type III system-associated effectors AvrPto1 and AvrPtoB, that are recognized and targeted by the effector-triggered immunity in tomato cultivars having the pto race-specific resistance gene. Race 1 strains instead lack the avrPto1 and avrPtoB genes and are therefore capable to aggressively attack all tomato cultivars. Here, we have performed the complete genome sequencing and the analysis of P. syringae pv. tomato strain DAPP-PG 215, which was described as a race 0 strain in 1996. Our analysis revealed that its genome comprises a 6.2 Mb circular chromosome and two plasmids (107 kb and 81 kb). The results indicate that the strain is phylogenetically closely related to strains Max13, K40, T1 and NYS-T1, all known race 1 strains. The chromosome of DAPP-PG 215 encodes race 1-associated genes like avrA and hopW1 and lacks race 0-associated genes like hopN1, giving it a race 1 genetic background. However, the genome harbors a complete ortholog of avrPto1, which allows the strain to display a race 0 phenotype. Comparative genomics with several PG01a genomes revealed that mobile DNA elements are rather involved in the evolution of the two different races.